Evaluasi Penggunaan Obat Antituberkulosis di Puskesmas Simpur Bandar Lampung - Karina Sinungan, Ulfa Mutia; Teodhora, Teodhora; Pratiwi, Ritha Widya (Program Studi S1 Farmasi, STIKES Senior, Medan, 2025)
Pulmonary tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Inappropriate use of antituberculosis drugs can cause failure to achieve therapeutic effectiveness, recurrence, and resistance to antituberculosis drugs. This study aimed to describe the characteristics of pulmonary tuberculosis patients, describe the use of pulmonary antituberculosis drugs, and evaluate the use of pulmonary antituberculosis drugs at the Simpur Inpatient Health Center, Bandar Lampung City, in 2021. This type of research was a descriptive observational cross-sectional design. Data collection was carried out retrospectively. The sampling technique used total sampling, with a total of 64 samples. The research instrument used was the medical records of pulmonary tuberculosis patients from January to December 2021. The results obtained were 38 male pulmonary tuberculosis patients (59.38%), an age range of 17–44 years (adults) for 34 patients (53.13%), type of pulmonary tuberculosis patients in new cases for 60 patients (93.75%), sputum examination results for AFB+ in 38 patients (59.38%), and category I treatment for 60 patients (93.75%). Evaluation of the use of pulmonary antituberculosis drugs obtained the results of the excellent indication (100%) and the right patient (100%), the proper drug selection (100%), the correct dose (95.31%), and the right time of drug administration (98.44%).